2021
DOI: 10.1016/j.compedu.2020.104096
|View full text |Cite
|
Sign up to set email alerts
|

The potential of 360-degree virtual reality videos to teach water-safety skills to children

Abstract: This study investigated the potential of Virtual Reality (VR), using 360-degree (360°) videos, as a tool to teach children about water-safety skills. Children (n = 182) aged 10 to 12 years were randomly assigned to learn about water safety using one of three instructional mediums: 2 360° VR videos, traditional video, or poster. The training was designed to address specific themes that contributed to drowning in coastal environments, allowing children to learn about dangers of rip currents in a relatively safe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 73 publications
(89 reference statements)
2
45
0
Order By: Relevance
“…Therefore, there is scope for future studies to build on this work by including a robust measure of cognitive load experienced by children when immersed in the VR and non-VR environments. Regarding engagement, although we did not measure this construct directly, there exist studies of adults showing high levels of engagement during training when using VR technology (e.g., Diego-Mas et al, 2020) and recent studies carried out in our lab have demonstrated that children show greater levels of engagement and enjoyment when learning through IVR compared to regular teaching tools (Araiza-Alba et al, 2020b, 2020c. A second limitation relates to possible confounding factors across the conditions.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
“…Therefore, there is scope for future studies to build on this work by including a robust measure of cognitive load experienced by children when immersed in the VR and non-VR environments. Regarding engagement, although we did not measure this construct directly, there exist studies of adults showing high levels of engagement during training when using VR technology (e.g., Diego-Mas et al, 2020) and recent studies carried out in our lab have demonstrated that children show greater levels of engagement and enjoyment when learning through IVR compared to regular teaching tools (Araiza-Alba et al, 2020b, 2020c. A second limitation relates to possible confounding factors across the conditions.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
“…A second study showed that 6-8 years olds benefited from video feedback when learning the flutter kick, but no effect was observed in younger children (4-6 years old) (Bunker et al, 1976). A promising recent study by Araiza-Alba et al (2021) suggests that virtual reality might become a powerful tool to help educate children about how to identify risks in open water environments such as rips at the beach (Araiza-Alba et al, 2021). There is a need for further studies investigating the use of new and increasingly accessible technologies such as waterproof cameras and virtual reality in teaching children aquatic skills.…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…These aspects can explain the increasing use of 360 °video by researchers and facilitators in education and training domains over the last 10 years (Reyna Zeballos, 2018). Currently, 360 °video are used in a wide range of domain, with students to change their preconceived notions on their career (Assilmia et al, 2017), or to create virtual field trips to integrate in future classrooms for PSTs (Huh, 2020), in medical education (Ulrich et al, 2019), sports training (basketball players; Panchuk et al, 2018, officials;Kittel et al, 2020a), or in water-safety skills to children (Araiza-Alba et al, 2021). The research field of 360 °video uses in TE is relatively recent and Reyna Zeballos, (2018) highlight that research in the field is not yet robust.…”
Section: Introductionmentioning
confidence: 99%